If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=2(-4)+3
We move all terms to the left:
y-(2(-4)+3)=0
We add all the numbers together, and all the variables
y+5=0
We move all terms containing y to the left, all other terms to the right
y=-5
| 9x²+4.7x-6=0 | | 13(y-5)=3(4y+4)-77 | | 5x+4x-4=-7 | | -24=-4x-8x | | 8=-10+3z | | y=4+5*9 | | -10x-3(x-1)=10-10x | | 14=4k+10 | | y=4+5*7 | | 10+4x=3x-1 | | y=4+5*4 | | 10x-3(x-1)=10-10x | | y=4+5*1 | | 7+5a-6a=3 | | b+9/12=-36 | | 6(4x-9)-23x=3 | | b+9/12=3 | | 4-2g=-4 | | -6+-4w=-14 | | 2y+4y+7y=3y^2 | | (10-4)=6(x+2) | | 24/15x-10/15x=4x/15x | | 22+x=2x-10 | | 2(13x-5)=13x-5+80 | | (7y-12)=(6y=8) | | x+40=2x14 | | 3m=6+12m | | 11/3x+11=4x-9 | | (24^2)x=28^2 | | 8+10(6-11)=-54+12x | | 7(x-3)=6(3x+1) | | 3x+12=1/2(4x+34) |